Religiosity as a Moderator of the Relationship between Personality Trait and Perceived Risk: A Conceptual Framework - ALSAHLIY, DALAL KHALID A; HUSIN, MAIZAITULAIDAWATI MD (The journal of contemporary issues in business and government, 2021)
This paper proposes a conceptual framework that considers religiosity as a moderator of the relationship between personality trait and perceived risk. This paper also examines five dimensions of personality traits in exploring the relationship of personality trait and perceived risk. The review finds that perceived risks towards financial products are affected by personality traits and influence by moderating factor; religiosity. Such an extensive review of examining variouspersonality traits to investigate the consumer perceived risk has not been done before. This paper will be useful to researchers, professionals and others concerned about understanding consumers' perceived risk when introducing new financial products and services.The proposed framework would lead to operational efficiencies through effective marketing strategies and a better understanding of the religiosity andcustomer traits.